Photo-Fenton degradation of the pharmaceuticals ciprofloxacin and fluoxetine after anaerobic pre-treatment of hospital effluent - Perini, João A. de Lima [UNESP]; Silva, Beatriz Costa e [UNESP]; Tonetti, Adriano L.; Nogueira, Raquel F. Pupo [UNESP] (Springer Nature, 2017)
This work evaluated the photo-Fenton degradation of two pharmaceuticals extensively used in human medicine, ciprofloxacin (CIP), and fluoxetine (FLU) when present in an anaerobic pre-treated hospital effluent (HE) at low concentration (100 μg L−1). Operational parameters such as concentration of hydrogen peroxide, iron, and initial pH as well as the effect of iron citrate complex were evaluated considering the degradation of the pharmaceuticals. Iron citrate complex (Fecit) influenced significantly FLU degradation at pH 4.5 achieving 80 % after 20 min, while with iron nitrate only 36 % degradation was obtained after the same time. However, only a slight effect was observed on CIP degradation, achieving 86 % with Fecit and 75 % with Fe(NO3)3, after 20 min. Samples of HE used in this work were previously treated in an anaerobic reactor followed by sand filtration; however, the presence of pharmaceuticals was detected. Degradation of both FLU and CIP was significantly hindered when present in HE, due to the relatively high content of organic (39.6 mg L−1) and inorganic (12.5 mg L−1) carbon, which may have consumed ·OH in side reactions. However, the iron cycle reduction was not affected by the matrix in the presence of citrate. Despite the recalcitrance of the matrix (no total organic carbon removal), it was possible to achieve over 50 % degradation of both pharmaceuticals after 90 min.
Keywords: Antibiotic; Antidepressant; Citrate; Hospital effluent; Iron complex